Assessment and training in Physical Education: conceptions and projections of future teachers in Colombia - Stieg, Ronildo (2025)
Assessment in the context of initial training can serve both as a methodological aspect and as a contribution to understanding the specific learning achieved by students in different training realities. Therefore, learning during Initial Teacher Training (FIP) should focus on ways of carrying out assessment that can serve as references for the future professional activity of teaching staff. In this sense, this article aims to analyze the assessment conceptions expressed by students of four FIP courses in Physical Education in Colombia. In addition, it seeks to understand what knowledge about educational assessment they have acquired throughout the course and how they project this knowledge into its future assessment practices. This study is part of a qualitative research, with the participation of 190 students from four Colombian institutions. The data were obtained through a questionnaire applied in 2022, and the narratives were analyzed with the IRAMUTEQ software. The results indicate that the student have knowledge about various assessment conceptions and approaches, as well as their implications for professional practice. They recognize that for effective assessment it is essential to employ varied and qualitative methods, and that the results should provide relevant information about learning, while encouraging feedback, self-confidence and socialization. In conclusion, the four FIP courses have promoted broad discussions on the topic, allowing future teaching staff to develop conceptual distinctions and reflect on the impact of each assessment approach on pedagogical practice.